Comparison of postoperative pain intensity after using reciprocating and continuous rotary glide path systems: a randomized clinical trial - Mehmet Adıgüzel; Koray Yılmaz; Pelin Tüfenkçi (Restorative Dentistry & Endodontics)
ObjectivesThe aim of this study was to compare postoperative pain intensity after root canal treatment with One G (OG) vs. R-Pilot (RP) files used for glide path preparation.Materials and MethodsNinety-three single-canaled mandibular premolar teeth with asymptomatic non-vital pulp were randomly assigned into 3 groups (n = 31): OG, RP, or without glide path (WGP). After creating the glide path, the root canals were prepared using sequential Mtwo rotary files to size 30/0.05. One endodontic specialist carried out single-visit endodontic treatment. The patients were asked to rate the severity of postoperative pain on a visual analogue scale at 24, 48, and 72 hours after the visit. They were also asked to record their intake of prescribed analgesics taken. The data were analyzed using the χ2, Friedman, Kruskal-Wallis, and Mann-Whitney U tests.ResultsIn all 3 groups, postoperative pain decreased significantly at each time interval (p < 0.05). At 24 hours, the OG group had less postoperative pain than the WGP group (p < 0.05). However, no significant difference was found between the RP group and the others. No statistically significant difference was found among the WGP, OG, and RP groups in postoperative pain intensity at 48 or 72 hours or in analgesic tablet intake at the 3 assessed time intervals.ConclusionsThe OG group had less postoperative pain than the WGP group in the first 24 hours. The OG and RP systems were similar regarding postoperative pain intensity and analgesic intake.